RESPON TANAMAN PAKCOY (Brassica rapa L) AKIBAT PEMBERIAN ZAT PENGATUR TUMBUH HORMONIK - Enny Mutryarny; Seprita Lidar (Jurnal Ilmiah Pertanian, 2018)
This study aims to know effect and find the best concentrate of Hormonik growing regulatory substances the growth and production of plants Pakcoy. The research was carried out in Complete Random design experiments (RAL) with 5 degrees of treatment with 4 replicates with parameters of observation is the height of plants, number of leaves, leaf width and heavy consumption. The data were analyzed statistically observations with prints, when F Count greater than or equal to F table 5%, followed by the test distance double Duncan in standard of 5%. The giving substance to a regulator grew Hormonikcan increase the growth and production of plants Pakcoy, with the best concentration is 4 cc/l water, it is advisable to further research with increased concentrations of Hormonik growing regulatory substances.